Catalytic Pauson–Khand Reaction in Ethylene Glycol–Toluene: Activity, Selectivity, and Catalyst Recycling - Cabré, Albert; Verdaguer, Xavier; Riera, Antoni (Synthesis, 2018)
The use of ethylene glycol (15% v/v in toluene) as additive in the catalytic Pauson–Khand reaction (PKR) is reported. In most cases both the yield and selectivity were enhanced compared to standard protocols. Moreover, the immiscibility of ethylene glycol in toluene allowed recycling of the catalyst (which remained mainly in the ethylene glycol). The recycling allowed catalyst loading to be reduced to only 3 mol%. A gram-scale reaction was also performed, allowing the use of only 1 mol% of Co2(CO)8, the lowest amount reported so far in intermolecular cobalt-catalyzed PKR.
Keywords: Pauson–Khand Reaction; homogeneous catalysis; cyclization; cobalt; additives; cyclopentenones; cycloaddition; catalyst recycling